Cross-Talk between PPARγ and Insulin Signaling and Modulation of Insulin Sensitivity - Anna Leonardini; Luigi Laviola; Sebastio Perrini; Annalisa Natalicchio; Francesco Giorgino (PPAR Research)
PPARγ activation in type 2 diabetic patients results in a marked improvement in insulin and glucose parameters, resulting from an improvement of whole-body insulin sensitivity. Adipose tissue is the major mediator of PPARγ action on insulin sensitivity. PPARγ activation in mature adipocytes induces the expression of a number of genes involved in the insulin signaling cascade, thereby improving insulin sensitivity. PPARγ is the master regulator of adipogenesis, thereby stimulating the production of small insulin-sensitive adipocytes. In addition to its importance in adipogenesis, PPARγ plays an important role in regulating lipid, metabolism in mature adipocytes by increasing fatty acid trapping. Finally, adipose tissue produces several cytokines that regulate energy homeostasis, lipid and glucose metabolism. Disturbances in the production of these factors may contribute to metabolic abnormalities, and PPARγ activation is also associated with beneficial effects on expression and secretion of a whole range of cytokines.